Effects of Incorrect Specification on the Finite Sample Properties of Full and Limited Information Estimators in DSGE Models - Sebastian Giesen; Rolf Scheufele (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2013)
In this paper we analyze the small sample properties of full information and limited information estimators in a potentially misspecified DSGE model. Therefore, we conduct a simulation study based on a standard New Keynesian model including price and wage rigidities. We then study the effects of omitted variable problems on the structural parameters estimates of the model. We find that FIML performs superior when the model is correctly specified. In cases where some of the model characteristics are omitted, the performance of FIML is highly unreliable, whereas GMM estimates remain approximately unbiased and significance tests are mostly reliable. – – In diesem Beitrag analysieren wir die Eigenschaften von verschiedenen Schätzern in einem potenziell fehlspezifizierten DSGE-Modell in kleinen Stichproben. Hierfür wird eine Simulationsstudie auf Basis eines neukeynesianischen Standardmodells durchgeführt. Es werden die Effekte von verschiedenen Fehlspezifikationen auf die Schätzer der strukturellen Parameter untersucht. Diese Studie zeigt, dass Full Informnation Maximum Likelihood überlegen ist, wenn das Modell korrekt spezifiziert ist. In Fällen, in denen einige Modelleigenschaften verändert werden, ist diese Methode jedoch höchst unzuverlässig, während Ansätze mit begrenzter Information (hier GMM) unverzerrt bleiben und auch Signifikanztests zuverlässiger sind.
urn:nbn:de:gbv:3:2-22479
Keywords: C26; C36; C51; E17; 330; FIML; GMM; finite sample bias; misspecification; Monte Carlo; DSGE; FIML; GMM; Kleinstichprobenverzerrung; Fehlspezifikation; Monte Carlo; DSGE